A rational approach in the sensory stimuli enhancement for the agnosic - S. Anitha Jebamani, Ms; R. Divya, Ms; K. Smruthi, Ms (International Journal of Engineering and Technology, 2018)
Life in todayâ€™s world has become very competitive and challenging. In this ambitious realm, learning, perception, application and expression are vital to every existential being. However, there are a few people around the world who are bereft of these fundamentals of liveli-hood. Agnosia is a disorder that exhibits the diminution of the ability to recognize objects, sounds or other sensory stimuli. It Is sometimes described as â€˜perception without meaningâ€™. The victim still has the knowledge of the object or the sound, but is unable to asso-ciate it meaningfully. There are varied dimensions of this disorder including visual, auditory and color agnosia.The aim of our project is to create a mobile application for the subjects of this disorder to be able to improve their recognition of objects, faces, sounds and colors through persistent practice and analysis. Illustrations of persons and objects with their descriptions for visual recognition, along with a verbal guide for identification and perception of sounds, and a color-picker to identify right colors will be equipped for study. Assessment criteria for evaluation of their performance will also be devised to keep in check their improvement, based on which graphical overviews and reports will be generated. A pulse sensor will also be appended to keep the pulse of the victim in check while on assessment. This methodical approach could be efficacious for the progression of sensory perception and recognition in the agno-sic.Â Â